Stitches to Riches? : Apparel Employment, Trade, and Economic Development in South Asia - Lopez-Acevedo, Gladys; Robertson, Raymond (Washington, DC: World Bank, 2016)
South Asia is in the midst of a demographic transition. For the next three decades, the growth of the region’s working age population will far outpace the growth of dependents. Close to one million individuals will enter the workforce every month. This large, economically active population can increase the region’s capacity to save and make crucial investments in physical capital, job training, and technological advancement. But for South Asia to realize these dividends, it must ensure that its working-age population is productively employed.